A global research trends of neuromarketing: 2015-2020 - Alsharif, Ahmed H. (2022)
he growth interesting in discovering the consumers’ behaviours, emotional and cognitive processes in marketing research have led to an increasing number of publications. This paper evaluates the global research trends in the neuromarketing/consumer neuroscience domain based on the most productive journals, countries, institutions, authors, the number of documents and citations. This paper was structured based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework in selecting all relevant documents for this bibliometric study. A total of 119 documents have been extracted and analysed from the Scopus database. The findings revealed that Spain is the leading country in this field of research with 21 publications, and the most productive institution was Universidad Complutense de Madrid, with seven documents. In addition, Ma, Q. is the most prolific author with four publications and 11 citations. Interestingly, although Frontiers in Psychology is the most productive journal with 11 publications, the Comunicar journal has the highest average citation per item. Keywords and citation analysis are highly significant to know the most impactful documents and words in neuromarketing. For example, EEG (18 occurrences and 43 total link strength) mean EEG occurrence 22 times, and total link strength for these occurrences are 43 links with neuromarketing theme. Chew L.H. et al., have published the most cited document with 27 citations. We believe that our study will provide a comprehensive overview of global trends in the neuromarketing domain.